Engineering for Rural Development 2019
DOI: 10.22616/erdev2019.18.n489
|View full text |Cite
|
Sign up to set email alerts
|

Methodical background of competence-based mathematics education for students of information technologies specialties

Abstract: Currently, the competence-based approach is the main task of higher education to prepare young professionals for a successful career and to ensure the country's socioeconomic growth. In order to implement the competence-based approach in practice, it is necessary to develop a methodical framework that includes mathematical competence and skills necessary for professional activities to be developed within a mathematical subject, including also personal qualities that are formed in mathematics studies. In the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…Es por esto que se considera que las matemáticas son una construcción única del pensamiento humano. A pesar de su alto nivel de abstracción y generalización, esta materia tiene vínculos fundamentales y vitales con nuestro mundo cotidiano, tanto en eventos diarios simples como en asuntos científicos sofisticados (Vintere & Briede, 2019).…”
Section: Metacogniciónunclassified
“…Es por esto que se considera que las matemáticas son una construcción única del pensamiento humano. A pesar de su alto nivel de abstracción y generalización, esta materia tiene vínculos fundamentales y vitales con nuestro mundo cotidiano, tanto en eventos diarios simples como en asuntos científicos sofisticados (Vintere & Briede, 2019).…”
Section: Metacogniciónunclassified
“…Due to the spread of information and communication technologies, digitalization, science, technology, engineering and mathematics [14,15] are becoming increasingly important for successful professional activities. The importance of mathematical training in engineering education and the relevance of its strengthening in some cases are shown in [16,17,18,19,20]. [21] carried out a theoretical and methodological study on the critical thinking THE METHOD OF A CONTINUOUS CONTROL-ASSESSMENT ACTIVITY "Consistency" ("testing through the whole course")…”
Section: Content Of the Decision Support System On The Example Of Matmentioning
confidence: 99%
“…On the same line, several studies conclude that mathematics presents di culties for middle and highereducation students (Strømgren et al 2014;Al Mutawah et al 2015;Milovanović 2020;Workman 2023) principally due to mathematics teachers frequently refraining from incorporating innovative strategies into math lessons despite their bene ts due to perceived irrelevance (Brozo et al 2017). Also, (Vintere and Briede 2019) Workman (Workman 2023), in his study about income inequality and student achievement, found that income inequality was associated with lower mathematics achievement. In this line, the problem is more frequent, especially in mid and low-income countries, due to a lack of continuous education, where there is a persistent inequality gap to access education, which means people with a stable economy have more opportunities to access better education.…”
Section: Introductionmentioning
confidence: 99%